Insights into Hsp90 mechanism and in vivo functions learned from studies in the yeast, Saccharomyces cerevisiae - Rios, Erick I.; Hunsberger, Isabel L.; Johnson, Jill L. (Frontiers in Molecular Biosciences, 2024)
The molecular chaperone Hsp90 (Heat shock protein, 90 kDa) is an abundant and essential cytosolic protein required for the stability and/or folding of hundreds of client proteins. Hsp90, along with helper cochaperone proteins, assists client protein folding in an ATP-dependent pathway. The laboratory of Susan Lindquist, in collaboration with other researchers, was the first to establish the yeast Saccharomyces cerevisiae as a model organism to study the functional interaction between Hsp90 and clients. Important insights from studies in her lab were that Hsp90 is essential, and that Hsp90 functions and cochaperone interactions are highly conserved between yeast and mammalian cells. Here, we describe key mechanistic insights into the Hsp90 folding cycle that were obtained using the yeast system. We highlight the early contributions of the laboratory of Susan Lindquist and extend our analysis into the broader use of the yeast system to analyze the understanding of the conformational cycle of Hsp90 and the impact of altered Hsp90 function on the proteome.